Bilingual Education Bilingual/Cross-Cultural Emphasis. Indian Legends and Felt Board Cut-Out Characters. Readings and Activities for Pre-School and Early Elementary School Classrooms - Bennett, Ruth.; California State Univ.-Humboldt, Arcata. Center for Community Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Designed for use in preschool and early elementary school classrooms, this collection of eight American Indian legends provides patterns for making feltboard cutouts of their characters and props to be used in story telling activities. Seven of the legends originate with the Hupa, Karuk, or Yurok Indians of northwestern California and one is from the Tlingit of the Pacific Northwest. Each legend is followed by patterns for its characters and props which include rabbits, blue jays, frogs, woodpeckers, eagles, squirrels, Indian maidens, foxes, coyotes, pine trees, tree stumps, camp fires, baskets, stars, and moons. The feltboard pieces can be made by students or made by the teacher and used in student performances. Pattern pieces have a simple outline with few internal details and an average size of 7 inches for the longer dimension. The legend titles are "Coyote and Crow,""Coyote and the Wren,""Coyote and the Stars,""Coyote and the Fox,""Coyote and Frog,""The Lonesome Little Pine Tree,""Deer and the Blue Jay," and "Blue Stone Man". A final section gives patterns for 25 additional mammals of the northwest. (JHZ)
ERIC Note: Some pages are marginally legible.
Educational level discussed: Early Childhood Education.
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Indian Culture; American Indian Education; American Indian Literature; Animals; Childrens Literature; Creative Activities; Cultural Education; Early Childhood Education; Legends; Manipulative Materials; Reading Aloud to Others; Reading Materials; Story Telling; Tribes; Flannel Boards; California -- Cultural Literacy -- Hupa (Tribe) -- Karuk (Tribe) -- Oral Tradition -- Tlingit (Tribe) -- Yurok (Tribe); Guides, Classroom -- Teacher